MASYARAKAT KAMPUNG ADAT CIREUNDEU DALAM PERSPEKTIF KEBUDAYAAN - Wulandari, Ratna Rizky; Tunur, Ajeng Syaripah; Salsabila, Syifa; Syafwan, Elvathna (Jurnal TEDC, 2024)
The Cireundeu indigenous village community is one of the Sundanese ethnic communities located and settled in Leuwigajah Village, South Cimahi District, Cimahi City. The Cireundeu village indigenous community is a society that is obedient in carrying out ancestral mandates. One of the behaviors passed down by the ancestors of the Cireundeu Village Indigenous Community to the residents as the next generation is the habit of consuming rasi (cassava pulp rice) as a staple. This research aims to provide an overview of the life of the Cireundeu Indigenous Village Community in a cultural perspective. The method used in this research is descriptive qualitative with observation, interview, and literature study techniques. The results of this study indicate that the Cirendeu Traditional Village Community has a rich culture and a strong social system. This encompasses a variety of aspects, including living equipment, livelihoods, kinship systems, languages, arts, knowledge, and religion. While the indigenous people of Cirendeu Village uphold the customs passed down by their ancestors, in terms of life, the Cireundeu indigenous people are also not much different from ordinary people. They carry out social life, socialize, and even attend school.